A case of severe hypothyroidism presenting only with bleeding diathesis (Indian Journal of Case Reports, 2015)
Hypothyroidism can present with the variety of clinical features; however, bleeding manifestations as a sole presentation of hypothyroidism is extremely rare. Hemostatic disorder may be a manifestation of several underlying etiology. Here, we report a case of a 14 year old girl who initially presented with bleeding diathesis without any other symptoms suggestive of thyroid dysfunction but later on investigations was found to be suffering from severe hypothyroidism.